Revitalization of Customary Law as a Source of Law in Environmental Protection in Indonesia - Kamakaula, Yohanes; Sagrim, Meky (PT. Anagata Sembagi Education, 2025)
This study aims to examine the position and role of customary law as a legal source in environmental protection efforts in Indonesia. Employing a normative juridical approach, the research analyzes statutory regulations, court decisions, and relevant legal documents to assess the extent to which customary law is recognized and implemented within the national environmental legal framework. The findings indicate that, constitutionally, customary law is acknowledged through Article 18B paragraph (2) of the 1945 Constitution. However, this recognition has not been fully followed by integration into sectoral laws such as the Environmental Protection Act, the Forestry Act, and the Mining Law. In fact, customary law holds significant potential in realizing ecological justice, as it embodies long-standing values of conservation, sustainability, and collective responsibility toward nature. Therefore, the revitalization of customary law is crucial through regulatory strengthening, the establishment of regional regulations recognizing Indigenous communities, and the harmonization of state and customary law. These efforts are expected to enhance environmental protection based on local wisdom.